Effects of three cutting blade designs on energy consumption during mowing-conditioning of Miscanthus Giganteus. (February 2018) - Gan, Hao; Mathanker, Sunil; Momin, Md Abdul; Kuhns, Brendan; Stoffel, Neal; Hansen, Alan; Grift, Tony
Abstract: This study compared energy consumption during harvest of Miscanthus Giganteus with a New Holland H8080 mower-conditioner among three cutting blade designs being 1) straight, 2) straight, angled at 30° and 3) serrated. Square bales were produced by a New Holland BB9080 large square baler. To calculate energy consumption per unit crop mass in MJ Mg −1, bales of known mass were identified, and the cutting energy to produce this bale was calculated by accumulating the mower-conditioner's energy consumption across the collection area associated with that bale. Energy consumption was also expressed as a Percentage of Inherent Heating Value (PIHV), where energy consumption was divided by the heating value of Miscanthus Giganteus (17.7 GJ Mg −1 ). Average energy requirement for the whole machine were 12.31 MJ Mg −1 (0.070 PIHV), 11.31 MJ Mg −1 (0.064 PIHV), and 9.27 MJ Mg −1 (0.052 PIHV) for straight, angled and serrated blades respectively. Average energy requirements for the header were 9.50 MJ Mg −1 (0.054 PIHV), 8.32 MJ Mg −1 (0.047 PIHV), and 7.20 MJ Mg −1 (0.041 PIHV) for straight, angled and serrated blades respectively. Average energy requirements for traction were 0.96 MJ Mg −1 (0.005 PIHV), 1.21 MJ Mg −1 (0.007 PIHV), and 1.04 MJ Mg −1 (0.006 PIHV) for straight, angled and serrated blades respectively. The theoretical field capacity increased from straight blades at 1.35 ha h −1 to angled blades at 1.52 ha h −1 to serrated blades at 2.23 ha h −1 . Evidently, the design of cutting blades had a significant effect on energy consumption and field performance of biomass harvesting equipment. Highlights: Three blade designs were compared in terms of cutting energy requirement. Serrated blade required 18.0% and 24.7% less energy than a 30° angled and 0° blade. The serrated blade improved the machine's field capacity in Miscanthus.